Di̇gi̇tal Li̇teraci̇es and Workplace on Start-Ups Ecosyst - Akpınar, Musab Talha (Current Studies in Management Information Systems, 2023)
Digital literacy is a crucial skill in the start-up ecosystem as it forms the foundation of how start-ups operate and reach their customers. Start-ups rely heavily on digital technologies and the internet to market their products and services, reach customers, and manage their operations. As a result, employees in start-ups need to have a strong set of digital literacy skills to be able to effectively use these tools and technologies. Digital literacy in start-ups includes not just the basic technical skills of using computers, software and internet, but also the ability to understand and use digital marketing, social media, e-commerce and other digital platforms to reach and engage customers. In addition, it includes data analytics, SEO and web design which are essential to have an online presence. Digital literacy is also important for employees in leadership roles as they are responsible for creating and implementing the digital strategy of the company. However, the start-up ecosystem is a fast-paced and constantly changing environment, where new technologies and digital tools are constantly emerging, making it important for employees to have a continuous process of learning and adapting to new technologies.